Second branchial cleft cyst with snoring during sleep as initial symptom: A case report and literature review. Issue 34 (27th August 2021) - Xian, Zhixiong; Chen, Yongchao; Teng, Yishu; Han, Saihong; Li, Lan
Abstract : Abstract: The second branchial cleft cyst lacks typical symptoms, and its clinical manifestations are complex and varied. Among them, the second branchial cleft cyst manifested by sleep snoring is relatively rare, and it can easily lead to missed diagnosis or misdiagnosis. This paper reports a case of a second branchial cleft abscess with snoring as the main manifestation. The branchial cleft cyst was removed using an endoscopic branchial cleft.